Tracing Language Transfer : Patterning English Pronunciation Through Arabic Sounds In Indonesia - Lestiono, Riski; Ismayoeng Gusdian, Rosalin (Erudio Journal of Educational Innovation, 2017)
This research aims to reveal how certain consonants existing in Arabic and English accommodate English for Foreign Language (EFL) students in Indonesia to pronounce English words. The data employed in this research were the sound transcriptions of two groups of English Language Education Department (ELED) freshmen of the University of Muhammadiyah Malang (UMM) when they pronounced several targeted consonants that were embedded into several chosen words. Based on the speech sound transcriptions of the first group of students who graduated from Islamic-based schools, the students were able to pronounce the targeted English sounds correctly. However, the second group showed that many of the students graduating from non-Islamic based schools made numerous errors; they replaced the targeted sounds with the nearest speech sounds.Key Words: Arabic consonant sounds; English consonant sounds; Indonesian EFL students